Pengaruh Biblioterapi “Teruslah Semangat Nadi” terhadap Stres Hospitalisasi Anak Pra Operasi - Nadhya Ayuningtyas; Aprina Aprina; Anita Anita (Politeknik Kesehatan Tanjung Karang, 2020)
Profile of Indonesian Children in Ministry Of Women Empowerment and Child Protection (2018), in 2017, children aged 0-17 years were diagnosed with a health complaint were 28,56%, while sick children (morbidity) were 15,86%. There is a need for psychological support so that children do not experience hospitalization stress by using storybooks that are constructive and optimistic to reduce stress on children in available health facilities. For a similarity between the child's condition and the content and meaning contained therein, the researcher used a storybook where there are similarities between hospitalized children and the contents of the story so that children can easily understand the contents of the story, this book is entitled